Toward a Spatiotemporal Model of Oxidation in Lipid Dispersions: A Hypothesis‐Driven Review. Issue 3 (16th January 2020) - Laguerre, Mickaël; Tenon, Mathieu; Bily, Antoine; Birtić, Simona
Abstract: Unsaturated lipids are prone to get oxidized through a sequence of reactions known as lipid oxidation. From a phenomenon considered at the beginning as a mere chemical process and described by the triptych of initiation, propagation, and termination, the vision of lipid oxidation has progressively evolved to further integrate the physical dimension of the phenomenon. Despite tremendous research efforts, however, this sequence of reactions is not yet well understood, especially in lipid dispersions where many facts are still inexplicable and unpredictable under the current paradigm. Here, the aim is to suggest that the main reason why a better understanding has not already been achieved is that the reactional network is not yet organized in a coherent spatiotemporal framework. The novel concepts and hypotheses proposed in this article may help redirecting a significant part of research efforts toward the establishment of a spatially and temporally resolved model of oxidation in dispersed lipids. Practical Application : Predicting how oxidation spreads in lipid dispersions represents a goal of crucial importance for academia but also for industry. Such prediction models would indeed greatly help food manufacturers prevent oxidation by using the most adapted antioxidative strategies for their specific products. To achieve such an objective, it is proposed that the first thing to do is to go beyond the extremely reductive and narrow framework in which this chemical process has been locked in. Indeed, while lipid dispersions are composed of a multitude of lipid colloids, researchers usually consider oxidation at the sole level of an individual droplet or membrane. Instead, lipid oxidation is advocated as a dynamic trafficking of chemical species within large communities of different colloidal objects such as droplets, membranes, or micelles dispersed in water—a system that dubbed "colloidal ecosystem". This might represent a scale complementary to the scales of individual colloids or molecules that were the sole consideration so far to try to represent lipid oxidation. Only then can one hope to effectively apply modeling and "omics" approaches, as is explained in more details in this article. Abstract : This work proposes that the initiation of the oxidation of dispersed lipids takes place at the oil/water interface and mainly involves decomposition of lipid hydroperoxides. Mass transport mechanisms of these species across large communities of colloids are also discussed. The hypotheses presented here may help redirecting part of the research efforts toward the establishment of a spatiotemporal model of lipid oxidation.